Evaluation of Phytosomal Curcumin as an Anti-inflammatory Agent for Chronic Glial Activation in the GFAP-IL6 Mouse Model - Ullah, Faheem; Liang, Huazheng; Niedermayer, Garry; Münch, Gerald; Gyengesi, Erika (Frontiers in Neuroscience, 2020)
Chronic glial activation is characterized by an increased number of activated microglia and astroglia; these secrete free radicals and cytotoxic cytokines, subsequently causing neuronal damage. This study investigated the hypothesis that a soy-lecithin based phytosomal curcumin can decrease glial activation in the brains of GFAP-IL6 mice, a model of chronic glial activation, which exhibits gliosis in various regions of the brain. Three doses of MC (874, 436 and 218 PPM) were fed to three-month-old GFAP-IL6 and wild-type (WT) mice for four weeks. As markers of glial activation, the total numbers of Iba-1+ and TSPO+ microglia and macrophages, and GFAP+ astrocytes, were determined in the cerebellum and hippocampus by immunohistochemistry and unbiased stereology. Furthermore, the morphology of the glial cells was assessed by confocal microscopy and Sholl analysis. Administration of phytosomal curcumin led to a dose-dependent reduction in neuroinflammatory markers. Phytosomal curcumin (874 PPM) decreased the number of microglia by 26.2% in the hippocampus and by 48% in the cerebellum of the GFAP-IL6 mice compared with the GFAP-Il6 mice on normal food. Additionally, GFAP+ astrocyte numbers in the hippocampus of the GFAP-IL6 mice were decreased by 42%. The GFAP-IL6 mice exhibited a different microglial morphology to the WT mice, showing an increased soma size and perimeter. This difference was significantly reduced by the 874 PPM phytosomal curcumin dose. Our findings demonstrate that phytosomal curcumin is able to attenuate the inflammatory pathology, and potentially reverse the detrimental effects of chronic glial activation.